2009
DOI: 10.1021/jp903234m
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Resonance Raman and Density Functional Theory Investigation of the Photochemistry of (S)-Ketoprofen

Abstract: Ketoprofen is known to induce photosensitivity due to its specific structure and electronic features, and this limits its use in medical applications. In this Article, the photochemistry of (S)-ketoprofen has been investigated by time-resolved resonance Raman spectroscopy to gain additional information so as to better elucidate the possible photochemical reaction mechanism of ketoprofen in different solvents. In nonaqueous solvents like neat acetonitrile and isopropyl alcohol, and 1:1 acetonitrile:water and 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 34 publications
6
71
0
Order By: Relevance
“…Comparison of the decarboxyation reactions studied here with previous results for the dissociated KP (KP À ) in basic solutions indicates that the dissociated KP (KP À ) undergoes a substantially faster decarboxylation reaction [16][17][18][19][20][21][22][23] than the undissociated KP (KP) examined in this investigation. This suggests that the undissociated and dissociated KP have noticeably different chemical reactivity toward decarboxylation and this may be an interesting issue to study further in the future.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Comparison of the decarboxyation reactions studied here with previous results for the dissociated KP (KP À ) in basic solutions indicates that the dissociated KP (KP À ) undergoes a substantially faster decarboxylation reaction [16][17][18][19][20][21][22][23] than the undissociated KP (KP) examined in this investigation. This suggests that the undissociated and dissociated KP have noticeably different chemical reactivity toward decarboxylation and this may be an interesting issue to study further in the future.…”
supporting
confidence: 71%
“…For example, a ketyl radical species is generated after the decay of 3 [KP] in 2-propanol solvent or in water solutions. [22,23] Previous studies indicated that water may play an important role in the photochemistry of the excited state. Ultrafast pump-probe spectroscopic studies on the hydrated 7-azaindole monomer provided evidence that an excited-state proton transfer can occur by means of a water proton bridge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of KP can lead to photosensitivity and phototoxicity because of its specific structure and electronic properties. The neutral form of ketoprofen that exists in the absence of a base displays typical benzophenone-like photochemistry 6 , while the deprotonated ketoprofen that exists in the presence of a base undergoes an efficient photodecarboxylation process 6,7 and therefore it appears that the photochemistry of KP is likely determined by the precursors, the neutral form of 3 [KP] or the deprotonated 3 [KP -1 ]. [2][3][4][5] These results revealed that the photochemistry of KP in aqueous solution is strongly affected by its acid-base chemistry.…”
Section: Water Concentration Dependent Photochemistry Of Ketoprofen Imentioning
confidence: 99%